A Systematic Review of the Effectiveness of Interventions to Prevent and Respond to Violence Against Persons With Disabilities. (November 2014) - Mikton, Christopher; Maguire, Holly; Shakespeare, Tom
Persons with disabilities make up some 15% of the world's population and are at higher risk of violence. Yet there is currently no systematic review of the effectiveness of interventions to prevent violence against them. Thus the aim of this review was to systematically search for, appraise the quality of, and synthesize the evidence for the effectiveness of interventions to prevent and mitigate the consequences of all the main forms of interpersonal violence against people with all types of disabilities. The method used consisted of searches of eleven electronic databases, hand searches of three journals, scanning of reference lists of review articles, contact with experts, appraisal of risk of bias using the Quality Assessment Tool for Quantitative Studies, and narrative synthesis of results. This resulted in 736 titles being identified, 10 of which met the inclusion criteria and 6 and 2 addressed people with intellectual disabilities and developmental disabilities, respectively. Only one was from a low- and middle-income country. All studies received a weak rating on the quality assessment tool and none could be considered effective after taking risk of bias into account. In sum, the current evidence base offers little guidance to policy makers, program commissioners, and persons with disabilities for selecting interventions. More and higher quality research is required, particularly from low- and middle-income countries and on other forms of disability such as physical impairments, sensory impairments, and mental health conditions.